Investigation of activation energies for dissociation of host‐guest complexes in the gas phase using low‐energy collision induced dissociation. (24th April 2019) - Bayat, Parisa; Gatineau, David; Lesage, Denis; Marhabaie, Sina; Martinez, Alexandre; Cole, Richard B.
Abstract: A low‐energy collision induced dissociation (CID) (low‐energy CID) approach that can determine both activation energy and activation entropy has been used to evaluate gas‐phase binding energies of host‐guest (H‐G) complexes of a heteroditopic hemicryptophane cage host (Zn (II)@1) with a series of biologically relevant guests. In order to use this approach, preliminary calibration of the effective temperature of ions undergoing resonance excitation is required. This was accomplished by employing blackbody infrared radiative dissociation (BIRD) which allows direct measurement of activation parameters. Activation energies and pre‐exponential factors were evaluated for more than 10 H‐G complexes via the use of low‐energy CID. The relatively long residence time of the ions inside the linear ion trap (maximum of 60 s) allowed the study of dissociations with rates below 1 s −1 . This possibility, along with the large size of the investigated ions, ensures the fulfilment of rapid energy exchange (REX) conditions and, as a consequence, accurate application of the Arrhenius equation. Compared with the BIRD technique, low‐energy CID allows access to higher effective temperatures, thereby permitting one to probe more endothermic decomposition pathways. Based on the measured activation parameters, guests bearing a phosphate (―OPO3 2− ) functional group were found to bind more strongly with the encapsulating cage than those having a sulfonate (―SO3 − ) group; however, the latter ones make stronger bonds than those with a carboxylate (―CO2 − ) group. In addition, it was observed that the presence of trimethylammonium (―N(CH3 )3 + ) or phenyl groups in the guest's structure improves the strength of H‐G interactions. The use of this technique is very straightforward, and it does not require any instrumental modifications. Thus, it can be applied to other H‐G chemistry studies where comparison of bond dissociation energies is of paramount importance.